Skip-beat! 18 - Nakamura, Yoshiki (Shojo beat manga., 2009)
"Kyoko hasn't had a Love Me Section job in a while, and this newest assignment is pushing her limits. She's now the personal assistant to Koo Hizuri, a Japanese actor turned Hollywood star, and everyone knows how assistants are treated in Hollywood! Can Kyoko see past Koo's meanness, or will his nastiness just make her demons worse?!" -- from publisher's web site.